Europäische rechtsgeschichte, immer noch ein projekt - Michael Stolleis (Clio@Themis)
The article describes the state of European Legal History as a discipline such as it has developed since the end of the Second World War. Major determinants were the Europe – euphoria of the Fiftieth, subsequently the gradual coalescence of the European Union, and eventually the return of the East – and South-East-European Nations to the free world. Yet”European Legal History“ as a well-defined discipline still is but a project. Perspectives of the future could be the following : To overcome nationalistic views when investigating pre-nationalistic periods of time, furthermore to join together sub-disciplines that define themselves by their respective sources (Roman Law, Canon Law, ius patrium), finally to extend the traditional legal history beyond civil law to the entire territory of law including non-state systems of norms. The aim should be twofold : To work out the particularities as well as the divergences of individual legal cultures in Europe, and to attempt at relating European and non-European legal cultures by means of historical comparison.